Iridium, carbon and nitrogen multiple-doped TiO2 Nanoparticles with enhanced photocatalytic activity. Issue 5 (1st April 2017) - Zhao, X.G.; Huang, L.Q.
Abstract: The aim of this research is to enhance the photocatalytic activity of TiO2 nanoparticles for the UV–visible light by multiple-doping with Iridium, carbon and nitrogen. The tridoped TiO2 photocatalyst were prepared by wet chemical method, and characterized by X-ray diffraction, Raman spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, ultraviolet-visible light diffuse reflection spectroscopy and room temperature photoluminescence spectroscopy. Besides, the photocatalytic H2 evolution performance of Ir-C-N tridoped TiO2 under UV–visible light irradiation was evaluated. It was found that Ir existed as Ir 4+ by substituting Ti in the lattice of TiO2 ; meanwhile, C and N were also incorporated into the surface of TiO2 nanoparticles in interstitial mode. Meanwhile, Ir-C-N tridoping extended the absorption of TiO2 into the visible light region and narrowed its band gap to ~3.0 eV, resulting in enhanced photocatalytic H2 evolution under UV–visible light irradiation. This could be attributed to narrow band gap and proper electronic structure of TiO2 after Ir-C-N tridoping.